Dampak Work-life Balance dalam Meningkatkan Komitmen Kerja melalui Motivasi Kerja pada Karyawan F&B Gen Z Jawa Tengah dan DIY - Amalia, Shifa Arfina; Ingsih, Kusni; Febriana, Artha; Purwatiningsih, Aris Puji (Jurnal EMT KITA, 2026)
This study aims to examine how the aligment between professionalism and personal activities affects work commitment, while also testing the extent to which work motivastion plays a role as a link in this corellation among Gen Z employees who work part-time in the food and beverage sector, especially in coffe shop in the DIY region, Central Java. Data collection was conducted through a questionnaire survey with a puposive sampling technique on 158 participants, after which is was analyzed through Partial Least Square Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 3 software. The research findings indicate that all hypotheses are accepted, namely work-life balance has a positive impact on work motivation and work commitment, with motivation as a partial mediator that strenghtens the corellation of harmony between work and personal life with commitment. Work motivation exhibits the strongest influence (path coefficient = 0,659). This study strengthens Boundary Theory through the finding that the harmony between professionalism and personal acts as a resource that drives intrinsic motivation and work commitment, especially in the context of part-time Gen Z employees in the food an beverage sector.